The Impact of Green Marketing Mix Practices on Customer’s Purchase Intention of Electric Vehicles in Palestine: The Mediating Role of Green Perceived Value - Saleh, Yahya; Alawneh, Thara’; Assaf, Ramiz; Attar, Hani; Kanan, Mohammad (Engineering, Technology & Applied Science Research, 2024)
This research aims to investigate the impact of a green marketing mix, involving green promotion and green pricing support practices, on the consumer’s intention to purchase Electric Vehicles (EVs) in Palestine, with the mediation role of Green Perceived Value (GPV). A quantitative method was used in this research, where relevant data were collected from a random sample via a structured distributed questionnaire which was answered by 53 respondents. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for the analysis. The model revealed that the green promotion and green price support practices, as well as GPV have a positive impact on customer intention to purchase EVs. Moreover, the results confirmed that GPV partially mediates the relation between green marketing mix practices and customer intention to purchase EVs. The results of this research present a guideline for marketing decision makers in automobile dealerships to improve customer EV purchase intention.